2019
DOI: 10.1002/cssc.201803063
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalysts for Electrocatalytic Oxidation of Ethanol

Abstract: The use of ethanol as a fuel in direct alcohol fuel cells depends not only on its ease of production from renewable sources, but also on overcoming the challenges of storage and transportation. In an ethanol‐based fuel cell, highly active electrocatalysts are required to break the C−C bond in ethanol for its complete oxidation at lower overpotentials, with the aim of increasing the cell performance, ethanol conversion rates, and fuel efficiency. In recent decades, the development of wet‐chemistry methods has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
113
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(115 citation statements)
references
References 282 publications
(468 reference statements)
0
113
0
2
Order By: Relevance
“…In addition„ the poor stability of commercial Pt/C catalysts is caused mainly by their unsatisfactory contact with the carbon support and spontaneous aggregation driven by surface‐energy minimization during the electro‐oxidation reaction . In addition, the carbon monoxide (CO)‐like intermediates formed in the alcohol oxidation reactions are absorbed on the catalyst surface, strongly affecting the long‐term performance and stability of these catalysts . Hence, the design and fabrication of highly efficient catalysts with satisfactory activity and stability are urgently needed for the further development of LFCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition„ the poor stability of commercial Pt/C catalysts is caused mainly by their unsatisfactory contact with the carbon support and spontaneous aggregation driven by surface‐energy minimization during the electro‐oxidation reaction . In addition, the carbon monoxide (CO)‐like intermediates formed in the alcohol oxidation reactions are absorbed on the catalyst surface, strongly affecting the long‐term performance and stability of these catalysts . Hence, the design and fabrication of highly efficient catalysts with satisfactory activity and stability are urgently needed for the further development of LFCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Guo et al. surveyed the studies on nanowires and nanotubes for efficient fuel cell electrocatalysts, but focused only on Pt‐based catalysts, Chen and co‐workers discussed different catalysts for ethanol electro‐oxidation, and the review by Wang et al. focused on the synthesis and application of multimetallic nanosheets .…”
Section: Introductionmentioning
confidence: 99%
“…SnO 2 provides OH species to oxidize adsorbed residues and enhances the formation of acetaldehyde and acetic acid. On the other hand, the addition of Rh further increases the EOR activity and stability by promoting the C-C bond cleavage, thus improving the electrocatalytic performance in DEFCs [29,[75][76][77]. In this context, Adzic's group showed by in situ infrared reflection-absorption spectroscopy (IRRAS) that the integrated band intensities of CO 2 (2343 cm −1 ), CH 3 CHO (933 cm −1 ), and CH 3 COOH (1280 cm −1 ) for both Pt-Rh-SnO 2 /C and Pt-SnO 2 /C samples proved the enhanced cleavage of the C-C bond in ethanol and all three constituents Pt, Rh, and SnO 2 are needed to gain the synergistic effect in facilitating the total oxidation of ethanol [78].…”
Section: Introductionmentioning
confidence: 99%
“…[1] It needs 12 electrons transfer to achieve the complete oxidation of ethanol in the electrocatalytic ethanol oxidation reaction (EOR), an essential reaction at the anode in DEFCs. [2,3] Electrocatalysts for EOR exhibit sufficient activity and enough durability. Extensive studies have demonstrated that Pd-based materials are excellent electrocatalysts for EOR.…”
mentioning
confidence: 99%
“…[6,26,27] PdTe 2 nanosheets show a higher ECSA value (43.2 m 2 g À1 Pd ) than that of Pd black (16.6 m 2 g À1 Pd ) at the positive inversion potential of 1.33 V vs RHE. Taking into account that full utilization of Pd would be 448 m 2 g À1 , the Pd In general, there are two major pathways for the ethanol oxidation process [30] CH 3…”
mentioning
confidence: 99%